Do mergers of potentially dominant firms foster innovation? An empirical analysis for the manufacturing sector - Elena Cefis; A. Sabidussi; E.J.J Schenk (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2007)
We investigate the effects of M&A on innovation in the specific context of potential or realized market dominance. Authorities are challenged by balancing both detrimental and beneficial effects of mergers on innovation, especially when a merger threatens to result in market dominance, while firms would wish to uncover all the potential benefits arising from M&A. The effects of M&As on innovation have been tested on a panel dataset, constructed from the Dutch Community Innovation Survey and the Dutch Business Register, including around 1000 manufacturing companies. We have adopted a comprehensive approach, taking into consideration three dimensions of innovation: innovation inputs, innovation outputs and efficiency. The results show that M&As performed in the previous 3-5 years have a positive and significant effect on innovation except R&D expenses and innovation efficiencies. The results also suggest that technological regimes are critical to understanding the patterns of innovation.
Keywords: 330; Mergers and Acquisitions; Innovation; Market Dominance